Efektifitas Pendidikan Kesehatan Dengan Media Audiovisual Dan Leaflet Terhadap Sikap Remaja Putri Menghadapi Menarche - Silalahi, Veronica (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: to identify the effectiveness of health education about menarche using audiovisual media and leaflets on the attitudes of teenage girls Methods: This article used a quasi-experimental non-equivalent control group design. This study divided the subjects into two groups, the intervention group and the control group with 31 respondents each, that is class III and IV in Sawunggaling 1 primary school, Surabaya. This article used a simple random sampling. Data processing was carried out by pretest and posttest and health education interventions using audiovisuals and leaflets for the intervention group, and for the control group using leaflet. Data analysis used the Mann Whitney test to assess the mean increase in attitudes in both groups, and the Wilcoxon test to see an increase in attitudes after the intervention in both groups.Results: The results showed p-value = 0.000 (p <0.05) in the intervention groups. This means that there is a significant increase in the attitude of teenage girls before and after being given health education which shows the effectiveness of health education about menarche using audiovisual media and leaflets. Whereas in the control group data obtained that 0.754 (p> 0.005), this means that there is no significant difference from the attitudes of teenage girls before and after being given health education about menarche with media leafletsConclusion : health education using audiovisuals and leaflets that are effective in improving the attitudes of teenage girls in facing menarcheÂ